Fluency Development Approach on Students’ Reading Accuracy and Comprehension Level - Losel Mae Abellana; Jeneifer Nueva (Journal of Research in Education and Pedagogy, 2025)
Fluency Development approach (FDA), also called Fluency Development Lesson, is a useful approach to teaching reading fluency that involves modeling fluency reading, assisted reading, repeated reading, word study, performance reading, and home and school involvement. It assessed the reading accuracy level in Word Count Per Minute (WCPM) of students before and after exposure to FDA, identified the comprehension level of students before and after exposure to FDA, determined the significant difference in the reading accuracy level of the students before and after exposure to FDA, and ascertained the significant difference in the reading comprehension of the students before and after exposure to fluency development approach. This determined the effect of the FDA on the reading skill of the Grade 8 frustrated readers of Kalilangan National High School for the school year 2017-2018. The study used a pretest-posttest experimental design, which involved the 38 respondents, identified based on the Diagnostic Reading Inventory test. Also, it utilized two instruments: The Fluency Accuracy: Assessment and Norms, focusing on the word count per minute (WCPM) and the Philippine Informal Reading Inventory (Phil-IRI) materials in assessing the accuracy and reading comprehension level of students. The results revealed that the reading accuracy and comprehension level of students showed a significant difference in the posttest results. Both reading accuracy and comprehension level of students improved in the posttest, but the improvement was not enough to reach the level required for Grade 8 high school students. Despite the limitations, it could still be concluded that the FDA helped improve students’ accuracy and comprehension level.